Continuous adductor canal block provides better performance after total knee arthroplasty compared with the single-shot adductor canal block?: An updated meta-analysis of randomized controlled trials. Issue 43 (23rd October 2020) - Yu, Rongguo; Wang, Haiyang; Zhuo, Youguang; Liu, Dongxin; Wu, Chunling; Zhang, Yiyuan
Abstract: Background: Adductor canal block (ACB) has emerged as an attractive alternative for femoral nerve blocks (FNB) as the peripheral nerve block of choice for total knee arthroplasty (TKA), preserving quadriceps motor function while providing analgesia comparable to FNB. However, its optimal application for TKA remains controversial. The objective of this meta-analysis was to compare continuous-injection ACB (CACB) vs single-injection ACB (SACB) for postoperative pain control in patients undergoing TKA. Methods: This study attempts to identify the available and relevant randomized controlled trials (RCTs) regarding the analgesic effects of CACB compared to SACB in patients undergoing TKA according to electronic databases, including PubMed, Medline, Web of Science, EMbase, and the Cochrane Library, up to September 2019. Primary outcomes in this regard included the use of a visual analogue scale (VAS) pain score with rest or activity, while secondary outcomes were cumulative opioid consumption, length of hospital stay (LOS), complications of vomiting and nausea, and rescue analgesia. The corresponding data were analyzed using RevMan v5.3. Ethical review: Because all of the data used in this systematic review and meta-analysis has been published, the ethical approval was not necessary Results: This research included 9 studies comprised of 739 patients. The analyzed outcomes demonstrated that patients who received CACB had a better at rest-VAS scores at 4 hours ( P = .007), 8 hors ( P < .0001), 12 hours ( P < .0001), 24 hours ( P = .02), mobilization-VAS score at 48 hours ( P < .0001), and rescue analgesia ( P = .03) than those who underwent SACB. Nevertheless, no significant differences were present between the 2 strategies in terms of pain VAS scores 48 hours at rest ( P = .23) and 24 hours at mobilization ( P = .10), complications of vomiting and nausea ( P = .42), and length of hospital stay ( P = .09). Conclusion: This meta-analysis indicated that CACB is superior to SACB in regard to analgesic effect following TKA. However, due to the variation of the included studies, no firm conclusions can be drawn. Further investigations into RCT are required for verification.